Dimensions of Religiosity in a Collection of Short Stories “War Breaks Again In Gaza” (Satu Pena Palestine Humanitarian Anthology) - Febriani, Avinda Elsa; Roziah, Roziah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study explores the dimensions of religiosity that appear in the short stories contained in the book